2012
DOI: 10.1016/j.amjcard.2011.09.049
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Count and Risk of Incident Atrial Fibrillation (From the Framingham Heart Study)

Abstract: Several studies have reported that inflammatory markers are associated with atrial fibrillation (AF). White blood cell (WBC) count is a widely available and broadly utilized marker of systemic inflammation. We sought to investigate the association between increased WBC count and incident AF, and whether this association is mediated by smoking, myocardial infarction and heart failure. We examined participants in the Framingham Heart Study Original Cohort. Cox proportional hazard regression analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 33 publications
1
53
1
3
Order By: Relevance
“…It was demonstrated that atrial fibrillation is closely associated with inflammation regardless of the duration of atrial fibrillation. However, this study showed no significant relationship between white blood cell count and risk of incident atrial fibrillation, which differs from the result of the Framingham Heart Study [19].…”
Section: Discussioncontrasting
confidence: 56%
“…It was demonstrated that atrial fibrillation is closely associated with inflammation regardless of the duration of atrial fibrillation. However, this study showed no significant relationship between white blood cell count and risk of incident atrial fibrillation, which differs from the result of the Framingham Heart Study [19].…”
Section: Discussioncontrasting
confidence: 56%
“…268 Subsequent studies have demonstrated relationships between several different serologic markers of inflammation and AF, including IL-6, 269 TNF-a, 270 aldosterone 271 and simple white blood cell counts. 272 Analyses of multiple inflammatory biomarkers within the same study have suggested that IL-6 and osteoprotegerin 273 may be especially important. The relationship between IL-6 and AF may be mediated by left atrial enlargement.…”
Section: Impact Of Atrial Cardiomyopathies On Occurrence Of Atrial Fimentioning
confidence: 99%
“…6,[13][14][15][16] More recently, a pro-inflammatory action of blood platelets has been proposed, 17 whereas the neutrophil-to-lymphocyte ratio better expresses an early inflammatory cellular response. 18,19 Evidence of the individual contribution of each of the above mentioned inflammatory biomarkers to different health outcomes is scarce.…”
mentioning
confidence: 99%